2010
DOI: 10.1080/03630242.2010.506153
|View full text |Cite
|
Sign up to set email alerts
|

Missed Opportunities to Prevent Perinatal Human Immunodeficiency Virus Transmission in 15 Jurisdictions in the United States During 2005–2008

Abstract: The objective of this study was to identify factors related to failure to receive recommended interventions for the prevention of mother-to-child HIV transmission among HIV-infected pregnant women in the United States. Using Enhanced Perinatal Surveillance data from 2005 through 2008, we identified characteristics of HIV-infected women (n = 5,391) that increased their odds of missing an opportunity to prevent perinatal HIV transmission. Adjusted odds ratios (aORs) and 95% confidence intervals (95% CIs) were ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…The results of the present study are consistent with previous studies of MTCT of HIV-1 conducted over the past 8 years in Europe [8,9], the USA [10,11], Africa [12], and Latin America and the Caribbean [2,13]. These studies identified various missed opportunities for prevention of infection, which included late or no HIV-1 testing [10–12]; late or no initiation of prenatal care or maternal antiretrovirals [2,8,10,11]; limited or no use of maternal antiretroviral regimens [2,9,11,13]; poor control of maternal VL during pregnancy [2]; and lack of ECD [2,11].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of the present study are consistent with previous studies of MTCT of HIV-1 conducted over the past 8 years in Europe [8,9], the USA [10,11], Africa [12], and Latin America and the Caribbean [2,13]. These studies identified various missed opportunities for prevention of infection, which included late or no HIV-1 testing [10–12]; late or no initiation of prenatal care or maternal antiretrovirals [2,8,10,11]; limited or no use of maternal antiretroviral regimens [2,9,11,13]; poor control of maternal VL during pregnancy [2]; and lack of ECD [2,11].…”
Section: Discussionsupporting
confidence: 93%
“…These studies identified various missed opportunities for prevention of infection, which included late or no HIV-1 testing [10–12]; late or no initiation of prenatal care or maternal antiretrovirals [2,8,10,11]; limited or no use of maternal antiretroviral regimens [2,9,11,13]; poor control of maternal VL during pregnancy [2]; and lack of ECD [2,11]. …”
Section: Discussionmentioning
confidence: 99%
“…The importance of substance abuse as a predictor of late diagnosis, suboptimal antiretroviral therapy and vertical HIV transmission was also shown by several studies from the United States and Europe. 3,7,9,[14][15][16] The observed lower uptake of antenatal combination antiretroviral therapy in the adjusted analysis for Ontario and Quebec compared to British Columbia/Yukon Territory may reflect, in part, the low uptake of such therapy among women who injected drugs in Ontario and Quebec. In this regard, it is noteworthy that the uptake of antenatal combination antiretroviral therapy was relatively uniform across maternal risk categories for all provinces except Ontario and Quebec.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, missing opportunities can jeopardize preventive measures. 8 In Goias State, central western Brazil, a special public health prenatal program ("Program for the Protection of Pregnant Women/PPPW") implemented in 2003 screens ∼70,000 pregnant women/year from ∼240 municipalities. Serological screening includes HIV-1, hepatitis B/C, Human T-LymphotropicVirus, syphilis, toxoplasmosis, rubella, Chagas' disease and Cytomegalovirus.…”
Section: Introductionmentioning
confidence: 99%